Developmental assets and positive youth development in Brazilian university students - de Jesus, Maurício Coelho; Dutra-Thomé, Luciana; Pereira, Anderson Siqueira (Frontiers in Psychology, 2022)
The Positive Youth Development (PYD) describes an intersection between young people and their context, emphasizing characteristics of a healthy development. The PYD’s 5Cs occur when there is an alignment between healthy individual characteristics and contextual resources. This study investigated the PYD’s 5Cs associations with the perception of social connections (family, community, academic), mental health, and stressful events. The sample was composed of 495 Brazilian College students aged between 18 and 33 years, who answered a survey with 59 questions about reflexive, constructive, and healthy behaviors. Descriptive, correlational, and regression analysis through structural equation modeling were conducted. The results focused on the role of family, community and educational institution in the PYD promotion. These results highlight the relevant contributions of social support in the construction of protective strategies of coping with stressful events and in the promotion of health behaviors and well-being, particularly in the university context.